Respuesta :

Answer:

Remember the "slope-intercept" form of a line:

y = mx + b

where

m = slope

b = y-intercept (0,b)

.

Simply "plug in" the given values into this form.

The problem gave you the fact that:

 

slope = m = 6

y intercept = b = -3

.

Therefore, from:

y = mx + b

we now have:

y = 6x + (-3)

or

y = 6x - 3

Answer:

y = 4x - 2

Step-by-step explanation:

The equation is y = mx + b

Slope: is m

Y-intercept: is b

Since your y-intercept is negative we have to subtract (*remember the sign in front of the number is its sign*)

your welcome

ACCESS MORE